Reaching Soldiers with Untreated Substance Use Disorder: Lessons Learned in the Development of a Marketing Campaign for the Warrior Check-Up Study - Walton, Thomas O. (Subst Use Misuse, 2013)
The Warrior Check-Up, a confidential telephone-delivered intervention, is designed to reach active-duty soldiers with untreated substance-use disorder at a large US military base. This paper describes the development and successful implementation of the study’s marketing strategies at the recruitment period’s midpoint (2010–2012). Qualitative analyses of focus groups (n = 26) and survey responses (n = 278) describe the process of campaign design. Measures of demographics, media exposure, post-traumatic stress, anxiety and depression gathered from callers (n = 172) are used in quantitative analysis assessing the campaign’s success in reaching this population. Implications, limitations, and suggestions for future research are discussed. Department of Defense provided study funding.